ANALISIS EFISIENSI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2012-2013 - Putra, Dichi Febrian (Jurnal Ekonomi Pembangunan, 2014)
The aims of this study is to measure and explain the efficiency level of bank listed on the Indonesia Stock Exchange (IDX) 2012-2013, as well as to analyze the composition of input and output that must be performed by an inefficient banking and the best reference for an inefficient banking on efficient banking. The data analysis technique that used in this study is using Data Envelopment Analysis (DEA) by using a model of Constant Return to Scale (CRS) consisting of the input variable (deposit, fixed assets, and the cost of labor) and output (loans). The result of this study indicated that the 33 banks listed on the Stock Exchange has an average technical efficiency of 86.72% in 2012 and 84.98% in 2013. Overall only six banks that have 100% value of efficiency in 2012, while in 2013 there are five banks which have 100% value of efficiency. Banks that have an efficiency value 100% can be a reference for a bank that has inefficient value which is under 100%. The cause of large inefficiency is because the disbursed loan variable has a value 81.81% on 2012 and 84.84% on 2013.